A population‐based prospective study of energy‐providing nutrients in relation to all‐cause cancer mortality and cancers of digestive organs mortality. Issue 10 (29th May 2013) - Argos, Maria; Melkonian, Stephanie; Parvez, Faruque; Rakibuz‐Zaman, Muhammad; Ahmed, Alauddin; Chen, Yu; Ahsan, Habibul
Abstract : The effect of dietary composition on mortality in low‐income countries is largely unknown. We evaluated whether percentages of dietary energy derived from protein, fat and carbohydrates were associated with all‐cause and cancer mortalities in a Bangladeshi population. Data from a prospective population‐based cohort study of 17, 244 men and women were used. Percentages of dietary energy derived from protein, fat and carbohydrates, assessed using a validated food‐frequency questionnaire at baseline, were analyzed in relation to mortality over an average of 9 years (155, 126 person‐years) of follow‐up. Cox proportional hazards regression models were used to estimate hazard ratios for all cause, all cancer and cancers of the digestive organs mortalities. Percentage of dietary energy from protein appeared to be significantly associated with cancer mortality. Fully adjusted hazard ratios for cancer mortality in increasing tertiles of percentage of dietary energy from protein were 1.0 (reference), 1.21 (0.73, 2.00) and 1.84 (1.08, 3.15) ( p for trend = 0.023). These associations were much stronger for deaths from cancers of the digestive organs with fully adjusted hazard ratios in increasing tertiles of percentage of dietary energy from protein being 1.0 (reference), 2.25 (0.91, 5.59) and 4.85 (1.88, 12.51) ( p for trend = 0.001). No significant associations in relation to cancer‐related mortality were observed for percentage of dietary energy from fat. Novel findings from this prospective study show protein is an important risk factor or proxy to an important risk factor for cancer mortality especially from digestive organ cancers in Bangladesh. © 2013 UICC Abstract : What's new? Cancer incidence and deaths are projected to increase in the coming years, mostly in developing countries. The amount of protein and fat in the diet has been associated with risk of digestive cancers in wealthy countries, but not in low income countries such as Bangladesh. The authors collected data on people's dietary habits and compared this with mortality over about 9 years. They found that protein consumption is associated with higher risk of death from digestive cancers among rural‐dwelling Bangladeshis.